Optimization of Labor Allocation to Maximize Cracker Production During Ramadan Using a Linear Program - Anita Putri Amelia; Ida Fitriana Ambarsari; Nur Hasanah (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2026)
The increase in demand for crackers during the Ramadan period requires optimal labor management to keep production efficient. This research aims to determine the optimal number of workers to maximize cracker production. The method used is linear programming with a simplex approach, with data obtained through interviews and processed using MATLAB. The model is formulated with a decision variable in the form of the number of workers at each stage of the production process. The purpose function is formulated to maximize total production by considering capacity constraints, operational time, and labor costs. The results of the study show that the optimal solution is obtained in . The maximum value of the objective function obtained is 80kg/day of production or equivalent to a 300% increase in cost efficiency per kg of Rp333.33. The allocation shows the most efficient distribution of labor in meeting resource limitations. Further research is recommended to consider dynamic demand factors and variations in production capacity.